Psychometric Properties of a Structured Diagnostic Interview for DSM-5 Anxiety, Mood, and Obsessive-Compulsive and Related Disorders. (January 2018) - Tolin, David F.; Gilliam, Christina; Wootton, Bethany M.; Bowe, William; Bragdon, Laura B.; Davis, Elizabeth; Hannan, Scott E.; Steinman, Shari A.; Worden, Blaise; Hallion, Lauren S.
Three hundred sixty-two adult patients were administered the Diagnostic Interview for Anxiety, Mood, and OCD and Related Neuropsychiatric Disorders (DIAMOND). Of these, 121 provided interrater reliability data, and 115 provided test–retest reliability data. Participants also completed a battery of self-report measures that assess symptoms of anxiety, mood, and obsessive-compulsive and related disorders. Interrater reliability of DIAMOND anxiety, mood, and obsessive-compulsive and related diagnoses ranged from very good to excellent. Test–retest reliability of DIAMOND diagnoses ranged from good to excellent. Convergent validity was established by significant between-group comparisons on applicable self-report measures for nearly all diagnoses. The results of the present study indicate that the DIAMOND is a promising semistructured diagnostic interview for DSM-5 disorders.